2016
DOI: 10.1088/1674-1056/25/9/097306
|View full text |Cite
|
Sign up to set email alerts
|

X-band inverse class-F GaN internally-matched power amplifier

Abstract: An X-band inverse class-F power amplifier is realized by a 1-mm AlGaN/GaN high electron mobility transistor (HEMT). The intrinsic and parasitic components inside the transistor, especially output capacitor C ds , influence the harmonic impedance heavily at the X-band, so compensation design is used for meeting the harmonic condition of inverse class-F on the current source plane. Experiment results show that, in the continuous-wave mode, the power amplifier achieves 61.7% power added efficiency (PAE), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is clear that the time exponent of the second stage is the same as that of the first stage, both stages meet the same degradation model, i.e., the H-H + reaction diffusion model. [16]…”
Section: Recovery Of Different Cyclesmentioning
confidence: 99%
“…It is clear that the time exponent of the second stage is the same as that of the first stage, both stages meet the same degradation model, i.e., the H-H + reaction diffusion model. [16]…”
Section: Recovery Of Different Cyclesmentioning
confidence: 99%
“…From the definition of the device threshold voltage, the negative drift of threshold voltage means the generation of positive charges, including the interface traps and the oxide traps during stress. [19] The preliminary study [20][21][22] has shown that under the action of holes in the inversion layer, the Si-H bond energy is weakened at the Si/SiO 2 interface. It brings about breaking of Si-H bonds at high temperature, which forms the dangling bond of silicon, namely, interface trap, and H + that can migrate into the oxide layer.…”
Section: Device Degradation Under Nbti Stressmentioning
confidence: 99%
“…Such works have expressed the benefits of such representation to accurately model the impact of gate resistance on cut‐off frequency (f T ), the maximum frequency of oscillation (f max ), noise parameters, and transconductance . To our knowledge, state‐of‐the‐art GaN MMIC circuits use models with lumped gate resistance . This paper makes it possible for the first time to highlight the interest of considering the distributed gate resistance on the performance of the GaN transistor and MMIC associated it.…”
Section: Introductionmentioning
confidence: 99%